Blend of 1 Butyl-3-methylimidazolium bis(Trifluoromethylsulfonyl)imide−monoethanolamine sulfolane as a novel non-aqueous solvent for carbon dioxide absorption and its thermophysical properties / Mohd Azlan Kassim - Mohd Azlan , Kassim (2018)
In this work, carbon dioxide (CO2) solubility studies and thermophysical properties were conducted on non-aqueous ternary mixtures of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([BMIM][NTf2]), monoethanolamine (MEA) and sulfolane carried out at various compositions and temperatures. CO2 solubility study conducted in this study was focused on the evaluation of [BMIM][NTf2] + MEA + sulfolane non-aqueous binary and ternary mixtures in absorbing CO2 at high pressure. The CO2 absorption experiment was conducted at pressure from 500 to 2000 kPa and temperatures ranging from 303.15 to 333.15 K. Highest CO2 loading was obtained by using 0B-30M (30 wt% MEA + 70 wt% sulfolane) binary mixture (2.224 – 2.861 mol CO2/ kg absorbent) and 5B-25M (5 wt% [BMIM][NTf2] + 25 wt% MEA + 70 wt% sulfolane) ternary mixture (1.882 – 2.705 mol CO2/ kg absorbent), at pressure range from 500 to 2000 kPa. Biphasic layer formation was observed in all mixtures containing MEA due to the formation of polar MEA-carbamate salt, which is insoluble in hydrophobic [BMIM][NTf2] and dipolar sulfolane. Compositions of the CO2-rich and CO2-lean layers were identified by 13C NMR. The CO2-rich layer can be easily separated and transported to the stripper to be regenerated. Thermophysical properties studies; density, viscosity and refractive index were conducted for [BMIM][NTf2] + sulfolane, MEA + sulfolane, [BMIM][NTf2] + MEA binary mixtures and [BMIM][NTf2] + MEA + sulfolane ternary mixtures over whole compositions at temperatures ranging from 303.15 to 343.15 K and at atmospheric pressure. Results show that the thermophysical properties of both binary and ternary mixtures demonstrate a composition and temperature-dependent behaviour. Thermophysical excess properties; excess molar volume, viscosity deviation and refractive index deviation were determined using experimental data to elucidate molecular interaction between molecules in both binary and ternary mixtures. Subsequently, the calculated excess properties were regressed to a Redlich-Kister equation. Molecular model using a conductor-like screening model for realistic solvation (COSMO-RS) computational method was conducted to determine the molecular interaction between components of binary and ternary over the whole range of composition. σ-profile, σ-potential, activity coefficient and excess enthalpies of each component of the composition described the polarity and H-bonding tendency of the molecules. Strong interaction between [BMIM][NTf2] and sulfolane was deduced while weaker interaction between MEA and both [BMIM][NTf2] and sulfolane in the binary mixtures. For [BMIM][NTf2]-MEA-sulfolane ternary mixtures, the predominant molecular interaction in the ternary mixtures would likely depend on the major binary mixtures present in the composition in the ternary mixtures.